2021
DOI: 10.1620/tjem.253.269
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles Before and After Exchange Transfusions in Severe Late-Onset Neonatal Group B Streptococcus Meningitis: A Case Report

Abstract: Streptococcus agalactiae or group B streptococcus (GBS) is a pathogen that causes severe neonatal infections, resulting in sepsis, pneumonia, and meningitis. Neonatal GBS meningitis has a poor neurological prognosis and a high mortality rate. GBS disease is classified as early-and late-onset if the onset age is 0-6 and 7-89 days after birth, respectively. There is currently no effective preventive strategy against late-onset GBS (LOGBS) disease. Here, we report a case of female infant with LOGBS meningitis who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Indeed, a dysregulated host response, characterized by excessive activation of the immune system, concomitantly with features of immune suppression, plays a central role in the pathogenesis of sepsis, and sepsis-related adverse outcomes in adults ( 23 ). In accordance with this concept, GBS infection is associated with strong systemic pro- and anti-inflammatory responses in newborns ( 21 , 22 , 70 ).…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, a dysregulated host response, characterized by excessive activation of the immune system, concomitantly with features of immune suppression, plays a central role in the pathogenesis of sepsis, and sepsis-related adverse outcomes in adults ( 23 ). In accordance with this concept, GBS infection is associated with strong systemic pro- and anti-inflammatory responses in newborns ( 21 , 22 , 70 ).…”
Section: Discussionmentioning
confidence: 73%
“…The cytokine profile of the infant was characterized by increases in TNFα and IL-1β that were about an order of magnitude lower than those seen during common neonatal sepsis 19 - 21) . However, IL-6, IL-8, G-CSF, and the anti-inflammatory cytokine IL-10 showed quite significant elevations.…”
Section: Discussionmentioning
confidence: 91%
“…Sugiura et al reported that in an extremely low-birthweight infant with septic shock due to necrotizing enterocolitis, the elevated serum IL-8 and calprotectin levels decreased after ET and the blood pressure increased and stabilized [ 24 ]. Moreover, Chishiki et al reported that ET saved the life of a neonate with septic shock due to severe Group B streptococcus meningitis, and that the procedure reduced the levels of both proinflammatory and anti-inflammatory cytokines [ 25 ]. Improvement of pulmonary perfusion, ventilation, and tissue oxygenation; Gottuso et al reported significantly improved pulmonary perfusion and ventilation after ET in low-birth-weight infants with severe respiratory distress [ 26 ].…”
Section: Exchange Transfusion As a Treatment Methods For Neonatal Sepsismentioning
confidence: 99%
“…Therefore, cytokine elimination therapy may improve the condition of neonates with sepsis. Although ET has been reported to have a cytokine elimination effect [ 24 , 25 ], the direct removal of inflammatory cytokines from whole blood using therapeutic PE is a potential alternative [ 63 ]. PE is a well-established therapeutic procedure commonly used in adults; it is based on the removal of plasma from whole blood followed by replacement of that volume with fresh frozen plasma.…”
Section: Plasma Exchange As An Alternative To Exchange Transfusionmentioning
confidence: 99%